(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2022)
Soy food is the second most consumed protein source in Indonesia. Unfortunately, more than 70% of yellow soybeans still imported since it could not be optimally cultivated in Indonesia. Indonesia has an indigenous black soybean (Glycine soja sieb), however it contains higher anti-nutrient content compared to the yellow one. Processing into tempeh milk were thought to improve its protein digestibility and reduce the levels of its anti-nutrient content. This study aimed to develop and evaluate the nutritional value of black soybean milk which is expected to improve the nutritional value and acceptability. According to its sensory and nutritional value, a ratio of water and tempeh 50:50 was chosen as the best formula. Proximate analysis proved an increase in protein content from black soybean (49.07) to tempeh (57.76) and decreased when it became tempeh milk (15.57%db). Evaluation of protein digestibility from black soybean (45) to tempeh (67) showed a significant improvement, while tempeh to tempeh milk (47.5%) didn’t show any significant differences. The improvement in protein digestibility was followed by the reduction of anti-nutrients in black soybeans, black soy tempeh, and black soy tempeh milk by 100, 58 and 50% respectively.